Farmers’ Perceptions and Knowledge towards Poplar based agroforestry: A Case Study in Terai Region of Kumaun - Kumar, Sandeep; Tewari, Sumit; Bijalwan, Arvind; Riyal, Manoj Kumar; Eripogu, Kiran Kumar (Indian Journal of Agroforestry, 2023)
The study aimed to identify farmers’ knowledge about tree farming and their perception towards poplar (Populus deltoids) based agroforestry in the Terai region of Kumaun, Uttarakhand, India. Primary data was collected through personal interviews of respondents through well-structured questionnaires. Personal observations were also done towards respondent farmers’ in each farmer class (i.e. marginal, small, semi-medium, medium, and large). The demographic profile from the present study revealed that the majority of farmers were middle-aged (52%), followed by old-aged (28%) and young-aged (20%) respectively. It is observed that more farmers are literate as the landholding capacity increases. It was also observed that farmers from all the classes have moderate to good knowledge about tree plantation and pruning techniques. Farmers in the study region were reluctant towards poplar plantation due to lower productivity of arable crops under agroforestry, low cost of poplar wood, crop damage by animals and birds, plantation of the tree inside farm boundary. Sugarcane as a cash crop is a major substitute for poplar agroforestry in the region. Exploring key interventions for enhancing crop yield and ensuring a good price of poplar wood through government help can be helpful in further adoption of poplar-based agroforestry.